Correlation of Dysplastic Changes of Squamous Epithelial Cells to Bacterial Vaginosis Based on Nugent Score in the Cervical Smears of Patients with Vaginal Discharge - Packirisamy Aruna; Kashish Arora (Asian Journal of Medical Research, 2020)
Background: Worldwide Cervical cancer is responsible for more than half a million new cases and a quarter of a million deaths annually.  Many Researches has established the causal role of oncogenic human Papillomavirus (HPV) infection in the pathogenesis of invasive cervical cancer and its precursor lesions. Bacterial vaginosis(BV) is one of the most common conditions of childbearing aged women worldwide, and considering a possible synergy of an imbalanced vaginal environment with cervical preneoplasia,it is clear that greater attention needs to be given to this condition. Objective: To find out an association between Nugent score and dysplastic epithelial cell changes in the cervical smears of patients with vaginal discharge.Subjects and Methods:This is a descriptive study conducted on 100 cervical smears from women of reproductive group with vaginal discharge.Paponicolaou stained and Gram stained smears were studied. The proportion of cervical smears with normal flora and dysplastic changes as well as that of smears with Bacterial vaginosis and dysplastic changes were calculated and compared.Results:19 smears were scored as BV,.2 out of 19 smears (10.5%)were showing epithelial cell abnormality.1 out of 38 (2.6%)smears having normal vaginal flora was reported as ASC and 6 out of 43(14%) smears in the intermediate category were reported as ASC(5) and  HSIL(1). Statistical analysis was done by Chi-square test using IBM-SPSS Statistics-22 statistical package.The correlation between Bacterial vaginosis and dysplastic changes were not found to be statistically significant.Conclusion: There is no definite correlation of Bacterial vaginosis with dysplastic changes in the cervical smear of patients with vaginal discharge related with the risk for cervical carcinogenesis. Evaluation of larger cohort of subjects over a prolonged time frame is required to assess the influence of Bacterial vaginosis in cervical carcinogenesis.